Applied principles of hydrology - Manning, John C. 1920- (Prentice Hall, 1997)
This book contains: The Water cycle; The Structure and Properties of Water; Water in the Air: Evaporation and Condensation; Precipitation; Infiltration and Soil Water; Evapotranspiration; Groundwater; Runoff; Chemical Quality of Natural Water; and The Water Cycle and Man.